Cunningham, Jr., Ed., Jefferson Vs. Hamilton - Confrontations That Shaped A Nation - Slater, Peter (Teaching History: A Journal of Methods, 2003)
Ask undergraduates about Thomas Jefferson and Alexander Hamilton and they will probably tell you that Jefferson was a president who had children with a slave mistress and that Hamilton was killed in a duel. One virtue of Noble E. Cunningham’s compilation of documents is that its emphasis is very different from these current ones. Jefferson vs. Hamilton focuses on how in the 1790s the two Revolutionary War patriots became bitter opponents and leaders of the first American political parties, a rivalry that continued until Hamilton’s untimely death during Jefferson’s first term.